Two endogenous Dictyostelium discoideum chemorepellents use different mechanisms to induce repulsion - Mohanad H. El-Sobky; Ramesh Rijal; Richard H. Gomer (Proceedings of the National Academy of Sciences, 2025)
The directed movement of eukaryotic cells is critical for processes such as development and immune responses. While much is known about chemoattraction, much less is known about chemorepulsion. The eukaryotic amoeba Dictyostelium discoideum secretes a 60 kDa chemorepellent protein called AprA to cause cells at the edge of a colony to move away from the colony. In addition to AprA, cells secrete a <10 kDa chemorepellent. Here, we show that the <10 kDa chemorepellent is a polymer of phosphates (polyphosphate; polyP). D. discoideum cells move by activating cortical Ras at one edge of the cell to initiate pseudopod formation. AprA induces repulsion by inhibiting Ras activation and pseudopod formation on the side of the cell closest to the source of AprA, without affecting the overall frequency of pseudopod formation. In contrast, polyP activates Ras at multiple regions of the cortex and increases pseudopod formation frequency, especially at the side of the cell furthest from the source of polyP. At least 20 signal transduction proteins are needed for both AprA and polyP repulsion, 9 are needed by polyP but not AprA, and 4 are needed by AprA but not polyP. Together, these results indicate that proliferating D. discoideum cells use two different chemorepellents, that one of the repellents is the unusual molecule polyphosphate, and that the two repellents activate partially overlapping and partially different pathways to induce repulsion by two basically different mechanisms.